Individual Patient Data Pooled Analysis of Randomized Trials of Bivalirudin versus Heparin in Acute Myocardial Infarction: Rationale and Methodology - Bikdeli, Behnood; McAndrew, Thomas; Crowley, Aaron; Chen, Shmuel; Mehdipoor, Ghazaleh; Redfors, Björn; Liu, Yangbo; Zhang, Zixuan; Liu, Mengdan; Zhang, Yiran; Francese, Dominic P.; Erlinge, David; James, Stefan K.; Han, Yaling; Li, Yi; Kastrati, Adnan; Schüpke, Stefanie; Stables, Rod H.; Shahzad, Adeel; Steg, Philippe Gabriel; Goldstein, Patrick; Frigoli, Enrico; Mehran, Roxana; Valgimigli, Marco; Stone, Gregg W. (Thrombosis and Haemostasis, 2020)
Background Individual randomized controlled trials (RCTs) of periprocedural anticoagulation with bivalirudin versus heparin during percutaneous coronary intervention (PCI) have reported conflicting results. Study-level meta-analyses lack granularity to adjust for confounders, explore heterogeneity, or identify subgroups that may particularly benefit or be harmed.Objective To overcome these limitations, we sought to develop an individual patient-data pooled database of RCTs comparing bivalirudin versus heparin.Methods We conducted a systematic review to identify RCTs in which ≥1,000 patients with acute myocardial infarction (AMI) undergoing PCI were randomized to bivalirudin versus heparin.Results From 738 identified studies, 8 RCTs met the prespecified criteria. The principal investigators of each study agreed to provide patient-level data. The data were pooled and checked for accuracy against trial publications, with discrepancies addressed by consulting with the trialists. Consensus-based definitions were created to resolve differing antithrombotic, procedural, and outcome definitions. The project required 3.5 years to complete, and the final database includes 27,409 patients (13,346 randomized to bivalirudin and 14,063 randomized to heparin).Conclusion We have created a large individual patient database of bivalirudin versus heparin RCTs in patients with AMI undergoing PCI. This endeavor may help identify the optimal periprocedural anticoagulation regimen for patient groups with different relative risks of adverse ischemic versus bleeding events, including those with ST-segment and non-ST-segment elevation MI, radial versus femoral access, use of a prolonged bivalirudin infusion or glycoprotein inhibitors, and others. Adherence to standardized techniques and rigorous validation processes should increase confidence in the accuracy and robustness of the results.
Keywords: bivalirudin; heparin; pooled analysis; percutaneous coronary intervention; acute myocardial infarction